Determinants of listed property stock performance in South Africa - Gulubane, Tlamelo (My University, 2017)
Despite the perceived superior performance of the South African listed property market and, even so, the recent introduction of Real Estate Investment Trust legislation to increase its global competitiveness, limited research exists on the market. This report thus examines the drivers of listed property performance from an economic and firm-specific perspective as well as providing an overview of the South African listed property market. The results of the study suggest that investors particularly earn a premium for holding stock with a low ratio of book-to-market value of equity. This study advances the knowledge of the South African listed property market, and further provides investors and fund managers alike with insight on the performance of listed property stock.
A research report submitted in partial fulfilment for the degree of Master of Science (Building) to the Faculty of Engineering and the Built Environment, School of Construction Economics and Management at the University of the Witwatersrand, Johannesburg, 2017
Keywords: Property--South Africa; Real estate investment--South Africa